Study of Morphofunctional Integrity of Platelets at Cryopreservation Stages - Kompaniets, A. M.; Knysh, O. V.; Gurina, T. M.; Bogdanchikova, O. A.; Ovsyannikov, S. E.; Pogrebnyak, M. L. (Problems of Cryobiology and Cryomedicine, 2006)
There were studied the effects of dimethyl sulfoxide (DMSO), dimethyl acetamide (DMAC), 1,2-propane diol (1,2-PD), their combination and two freezing programs on morphofunctional properties of human donor blood platelets at cryopreservation stages. The highest indices of platelet integrity were shown to be obtained at their cryopreservation with DMSO and when combining 1,2-PD with DMAC in 0.7 M final concentration during freezing according to the program with overcooling elimination. The results obtained testify to the necessity in elaborating the polycomponent cryoprotective media for platelet cryopreservation and perspectiveness in investigating special freezing programs with a controlled rate of passing through temperature interval of crystallisation.